2017
DOI: 10.9790/0837-2206111422
|View full text |Cite
|
Sign up to set email alerts
|

Examining Organizational Commitment and Psychological Capital in Indian Bank Employees

Abstract: Abstract:The objective of the present research was to understand the sector differences (public vs. private) in Indian banks on organisational commitment. The study also tries to understand the relationship between psychological capital and organisational commitment in the banking sector. The sample comprised of 147 middle level managers, above 25 years of age, working in public and private banks. The organizational commitment questionnaire and the psychological capital questionnaire were administered and desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…This implies that workplace resilience is positively correlated with organizational commitment. The result of the study confirms with various authors (Jain & Kumar, 2017;Polat & İskender, 2018) who mentioned that if an organization wants to increase its employees' commitment, it must focus on its psychological capital by offering interventions that target its employees' hope, self-efficacy, resilience, and optimism. As resilience levels increase, peopl e will become more committed to their organizations.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This implies that workplace resilience is positively correlated with organizational commitment. The result of the study confirms with various authors (Jain & Kumar, 2017;Polat & İskender, 2018) who mentioned that if an organization wants to increase its employees' commitment, it must focus on its psychological capital by offering interventions that target its employees' hope, self-efficacy, resilience, and optimism. As resilience levels increase, peopl e will become more committed to their organizations.…”
Section: Resultssupporting
confidence: 83%
“…If an organization wants to increase its employees' commitment, it must focus on its psychological capital by offering interventions that target its employees' hope, selfefficacy, resilience, and optimism (Jain & Kumar, 2017). There is a significant positive relationship between resilience and organizational commitment.…”
Section: Correlation Between Measuresmentioning
confidence: 99%
“…Psychological Capital and Work-Related Outcomes. Prior research has found that PsyCap has a significant impact on enhancing desirable work outcomes, such as job satisfaction (Badran & Youssef-Morgan, 2015;Luthans et al, 2007;Nafei, 2015), organizational commitment (Jain & Kumar, 2017;Luthans et al, 2007;Nafei, 2015), organizational citizenship behavior (Beal et al, 2013;Bouzari & Karatepe, 2017;Nafei, 2015), and performance (Bouckenooghe et al, 2015;Carmona-Halty et al, 2018;Sen & Basim, 2018). PsyCap also reduced undesirable work-related outcomes such as turnover intentions (Agarwal, 2018;Gupta & Shaheen, 2017), deviant behavior (Avey et al, 2012;Norman et al, 2010), cynicism (Avey et al, 2012;Akcay, 2018;Sen & Basim, 2018;Stratman & Youssef-Morgan, 2019), and workplace incivility (Hashemi et al, 2018;Roberts et al, 2011).…”
Section: Hypothesis Developmentmentioning
confidence: 99%